A method for processing 4N6 grade high-purity quartz using granite pegmatite as raw material
Through multiple steps, including crushing, screening, burning, water quenching, grinding, magnetic selection, floating, water heat treatment, ultrasonic acid immersion and chloride roasting, etc., the gaseous liquid wrap and impurities of granite gantry in the Guangangye crystal rock and impurities of impurities and impurities The removal problem of ions realizes the production of high -purity quartz sand, which improves the added value of the product and the adaptability of industrialized application.
Patent Information
- Application Number
- CN202410704011.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The existing high-purity quartz sand purification process is difficult to remove gas-liquid inclusions and structural impurities in granite to the maximum extent, resulting in low added value of the product, high energy consumption and serious environmental protection problems.
The multi -step process includes crushing, screening, burning, water quenching, grinding, magnetic selection, floating, water heat treatment, ultrasonic acid immersion and chloride roasting, etc. Remove impurities and further remove miscellaneous steps through water heat treatment and ultrasonic acid immersion, and finally obtain high -purity quartz sand through chloride and roasting.
It achieves effective removal of gas-liquid inclusions and impurity ions, improves the purity and added value of high-purity quartz sand, reduces production costs and environmental impact, and is suitable for industrial applications.
Smart Images

Figure CN118495541B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-purity quartz processing, and in particular to a method for processing 4N6-grade high-purity quartz using granite pegmatite as a raw material. Background Art
[0002] High-purity quartz is a scarce strategic mineral resource in the world. Although the ore types are diverse and the resources are abundant, different quartz raw materials have great differences in ore properties. With the reduction and shortage of high-quality resources such as crystal and vein quartz, the existing technology mostly uses granite pegmatite (composed of minerals such as feldspar, quartz, mica, etc., which crystallize into huge crystals under high temperature and high pressure environment), formerly known as white granite, as raw material to produce high-purity quartz sand. Granite pegmatite is formed by the slow solidification of underground mantle magma, so the gas-liquid inclusions and hydroxyl content inside are very low, and the high-purity quartz sand produced has excellent performance and occupies a dominant position in the field of high-purity quartz sand in the world.
[0003] However, granite pegmatite ore usually contains a large number of structural impurities, such as gas-liquid inclusions and structural impurity ions. These structural impurities are the main factors that form impurity defects in downstream products. The content of inclusions is a decisive factor affecting many properties of quartz, and it is also the focus and difficulty of impurity removal of high-purity quartz sand. The traditional high-purity quartz sand purification process is difficult to remove gas-liquid inclusions and impurity ions to the maximum extent, and often has environmental problems such as low product added value, energy consumption, and large amounts of leaching waste liquid. It often cannot achieve ideal production results and affects promotion and industrial application. At present, the most effective means is to explore quartz ores with fewer structural impurities (especially gas-liquid inclusions), and existing research results show that various technical means for removing gas-liquid inclusions have certain limitations.
[0004] In summary, in view of the current status and problems of high-purity quartz beneficiation and purification technology, it is urgent to study a granite pegmatite as a preferred ore source for high-purity quartz, and to specifically remove structural impurities in high-purity quartz sand raw materials, such as gas-liquid inclusions and impurity ions in the lattice, through a combined beneficiation and purification process. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a method for processing 4N6 grade high-purity quartz using granite pegmatite as raw material.
[0006] The present invention protects a method for processing 4N6 grade high-purity quartz using granite pegmatite as raw material, which specifically comprises the following steps:
[0007] Step 1, crushing: wash the granite pegmatite until the surface is clean, first use large and medium jaw crushers to coarsely crush the ore raw materials; then use corundum liner small jaw crusher and corundum double roll crusher for fine crushing;
[0008] Step 2, screening: Take the ore crushed in step 1, use a 30mm standard sieve for wet screening, and pre-select the ore materials ≥30mm through an X-ray intelligent machine and then perform the crushing and screening steps again;
[0009] Step 3, calcination: place the fine-grained ore material with a particle size of less than 30 mm after screening in step 2 in a muffle furnace and heat it to 1300±10°C for 1 hour;
[0010] Step 4, water quenching: take out the calcined ore, quench with deionized water to cool it down to 750°C to 800°C, repeat the calcination and water quenching steps three times, take out the ore, and quench with deionized water to cool it down to room temperature;
[0011] Step 5, drying and grinding: the ore after water quenching is placed in an oven at 105°C for 2 hours, cooled to room temperature and then ground to less than 60 mesh (0.42 mm);
[0012] Step 6, classification: the ground ore is screened and classified into 60 mesh (0.250 mm) to 80 mesh (0.178 mm), 80 mesh (0.178 mm) to 120 mesh (0.125 mm), 120 mesh (0.125 mm) to 170 mesh (0.09 mm), and <170 mesh (0.09 mm);
[0013] Step 7, magnetic separation: add the classified mineral materials to the magnetic separator respectively, and select them twice at a magnetic induction intensity of 1.4T;
[0014] Step 8, flotation separation: the ore materials after magnetic separation are added to the flotation machine respectively, and flotation separation is carried out for 5 minutes under the conditions of pH 3, 120 g / t of dodecylamine collector, and HF as a regulator. After flotation, the quartz sand is washed with ultrapure water to neutrality, and dried to obtain quartz concentrates of different particle sizes;
[0015] Step 9, hydrothermal treatment: quartz sand concentrate, amorphous nano-SiO2 powder and alkaline solution are mixed in a certain solid-liquid ratio to obtain a mixed solution; the mixed solution is placed in a hydrothermal reactor, and a hydrothermal reaction is carried out for 24 to 48 hours under closed, constant temperature and certain saturated water vapor pressure conditions; after the reaction, the mixed solution is filtered, washed with deionized water to neutrality, and dried to obtain quartz sand concentrate;
[0016] Step 10, ultrasonic acid leaching: the quartz sand concentrate after hydrothermal treatment is subjected to ultrasonic acid leaching, the ultrasonic frequency is 70KHz, the acid leaching condition is a solid-liquid mass ratio of 1:5, and a mixed acid solution is used for treatment, and the mixed acid volume ratio is V 盐酸 :V 硝酸 :V 氢氟酸=1:1:2; the acid leaching reaction conditions are 60°C ultrasonic assisted reaction for 120 min; the quartz sand concentrate after acid leaching is rinsed with deionized water to neutrality and dried;
[0017] Step 11, chlorination roasting: the ore after ultrasonic acid leaching and drying is placed in a chlorination roasting device for purification treatment, and after treatment, it is washed with 10% dilute hydrochloric acid and dried to obtain high-purity quartz sand products with SiO2>99.996% and a total impurity element content of less than 38ug / g of different particle sizes.
[0018] Furthermore, in step 8, reverse flotation conditions are used in the flotation separation.
[0019] Furthermore, in the hydrothermal treatment of step 9, the solid-liquid mass ratio of the quartz sand concentrate, the amorphous nano-SiO2 powder and the alkaline solution sodium hydroxide solution in the mixed solution is 1:2; the temperature of the hydrothermal treatment is 250°C, the pH value is ≥10, and the saturated water vapor pressure is 1.4-4.5MPa.
[0020] Furthermore, the mixed acid concentrations of the ultrasonic acid leaching in step 10 are 30% hydrochloric acid, 70% nitric acid, and 40% hydrofluoric acid.
[0021] Furthermore, the temperature of the chlorination roasting in step 11 is 1200-1400° C., the time is 0.5-1 h, and the chlorination gas introduced is HCl.
[0022] Furthermore, the ore sample after chlorination roasting in step 11 needs to be repeatedly washed with 10% dilute hydrochloric acid until no Cl can be detected with AgNO3. - .
[0023] Furthermore, the drying conditions in steps 8-11 are all kept at 105° C. for 2 hours.
[0024] Compared with the existing technology, the present invention has the following beneficial effects:
[0025] Compared with the traditional high-purity quartz sand purification process, the method of the present invention can remove gas-liquid inclusions and impurity ions to the maximum extent, and the product has high purity and is easy to be applied in industry. Specifically, multiple high-temperature calcination and water quenching expose inclusions and lattice impurities to the outside, and grinding and screening classify quartz particles of different particle sizes and different impurity contents; the 1.4T medium magnetic field intensity significantly reduces the content of Fe2O3, Al2O3, and TiO2 in the concentrate; the reverse flotation conditions of pH 3, dodecylamine collector 120g / t, and HF as a regulator obtain the quartz sand concentrate with the highest SiO2 content and recovery rate; high-temperature and high-pressure hydrothermal treatment, ultrasonic acid leaching and chlorination roasting fully remove the structural impurities in the quartz sand, and obtain a high-purity quartz sand concentrate with w(SiO2)>99.996% and a total content of impurity elements <38ug / g. The product has a narrow particle size range, and can produce high-purity quartz with particle sizes of 60 mesh (0.250mm) to 80 mesh (0.178mm), 80 mesh (0.178mm) to 120 mesh (0.125mm), 120 mesh (0.125mm) to 170 mesh (0.09mm), and <170 mesh (0.09mm). BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a process flow chart of the method. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] 1. Test samples
[0030] The experimental samples used in the present invention are the granite pegmatite ore from XX in Qinghai as the research object, and a total of 3 replicate samples are taken; the granite pegmatite ore is white, grayish yellow, and dense and massive. Table 1 is the inductively coupled plasma optical emission spectrometry (ICP-OES) test results of the granite pegmatite ore samples used in the experiment:
[0031] Table 1 Chemical composition of the original granite pegmatite ore from XX area in Qinghai
[0032]
[0033]
[0034] 2. Water quenching process condition test
[0035] The impurities that are more difficult to remove in the granite pegmatite raw materials are gas-liquid inclusions and structural impurity ions in the lattice. When the gas-liquid inclusions are subjected to high-temperature calcination and rapid cooling by water quenching, their bodies undergo multiple drastic changes, which cause concentrated stress and cracks to be generated along the interface between the inclusions and the quartz sand, thereby exposing the inclusions to the outside world and causing the quartz crystal form to change, so that the lattice impurities are enriched on the surface of the quartz sand. Better removal in the subsequent mineral processing process is one of the main key technical issues of the present invention.
[0036] Li Gaoshan et al. concluded in "Minerals Do Not All Expand and Contract When Heat is Heated" that the thermal expansion rate of quartz in each crystal axis direction increases during the heating process, reaches a maximum at about 573°C, and then slowly contracts. The present invention tests the volume thermal expansion rate of quartz particles of granite pegmatite in XX, Qinghai, and the results are shown in Table 2:
[0037] Table 2 Volume thermal expansion rate of quartz particles in the granite pegmatite in XX area of Qinghai
[0038]
[0039] From the test results in Table 2, it can be seen that the volume thermal expansion coefficient of quartz particles in granite pegmatite reaches its maximum when it is close to 800°C, which is not much different from the volume thermal expansion coefficient at 700°C. Therefore, in the water quenching process, the best temperature is 750°C to 800°C.
[0040] 3. Hydrothermal treatment process conditions test
[0041] In the process of crystal growth, isomorphism often occurs, such as Al 3+ With Si in quartz 4+ Substitution into the lattice to become the main support, while introducing K + , Li + These ions constitute structural impurities in quartz and are difficult to remove, becoming the main factor hindering the development and application of quartz. 4+ The removal of impurity ions by substitution reaction is one of the main key technical issues of the present invention.
[0042] The steps of this test are: Step 1: Mix quartz sand concentrate, amorphous nano-SiO2 powder and alkaline solution (pH ≥ 10) in a certain solid-liquid ratio to obtain a mixed solution; Step 2: Place the mixed solution in a hydrothermal reactor for hydrothermal reaction under closed, constant temperature and saturated water vapor pressure conditions; Step 3: Filter the mixed solution after the reaction, wash it with deionized water to neutrality, and dry it to obtain quartz sand concentrate, and analyze its impurity content. The specific experimental plan and test results are shown in Table 3.
[0043] Table 3 Hydrothermal treatment conditions and results
[0044]
[0045]
[0046] According to the data in Table 3, the optimized process conditions for hydrothermal processing of high-purity quartz using granite pegmatite as raw material can be summarized, namely: the solid-liquid mass ratio of quartz sand concentrate, amorphous nano-SiO2 powder and alkaline solution sodium hydroxide solution in the mixed solution is 1:2; the hydrothermal treatment temperature is 250℃, the time is 24h~48h, the pH value is ≥10, and the saturated water vapor pressure is 1.4~4.5MPa.
[0047] 4. Acid leaching process conditions test
[0048] After the granite pegmatite is diagenetic, under the influence of later geological actions, the mineral composition, structural structure, chemical composition and inclusion characteristics of granite pegmatites from different origins are very different. Determining the temperature, material particle size, acid concentration and other conditions required for acid leaching according to the properties and characteristics of granite pegmatite minerals from different origins is one of the main key technical issues of the present invention.
[0049] Taking the beneficiation and purification test of granite pegmatite in a certain place in Qinghai as an example, hydrochloric acid (HCl) with a purity of 30% purchased from Xinhui Chemical Products Company in Chengbei, Xining, nitric acid (HNO3) with a purity of 70%, and hydrofluoric acid (HF) with a purity of 40% were selected as acid reagents to carry out the optimization test of the acid leaching process (see Table 4 for details).
[0050] Table 4 Acid leaching process test design
[0051]
[0052]
[0053] Table 5 Acid leaching process test results (“—” indicates the content is lower than the detection limit)
[0054]
[0055]
[0056] According to the data in Table 4 and Table 5, the optimized process conditions for acid leaching and purification of high-purity quartz using granite pegmatite as raw material can be summarized, namely: using mixed acid for treatment, the mixed acid volume ratio is V 盐酸 :V 硝酸 :V 氢氟酸 =1:1:2, solid-liquid mass ratio is 1:5, acid leaching temperature is 60℃, ultrasonic-assisted reaction time is 2h, and as the particle size of quartz concentrate is smaller, the impurity content is lower, and ω(SiO2) is higher.
[0057] Example 2
[0058] A method for processing 4N6 grade high-purity quartz using granite pegmatite as raw material, specifically comprising the following steps:
[0059] Step 1, crushing: wash the granite pegmatite until the surface is clean, first use large and medium jaw crushers to coarsely crush the ore raw materials; then use corundum liner small jaw crusher and corundum double roll crusher for fine crushing;
[0060] Step 2, screening: Take the ore crushed in step 1, use a 30mm standard sieve for wet screening, and pre-select the ore materials ≥30mm through an X-ray intelligent machine and then perform the crushing and screening steps again;
[0061] Step 3, calcination: place the fine-grained ore material with a particle size of less than 30 mm after screening in step 2 in a muffle furnace and heat it to 1300±10°C for 1 hour;
[0062] Step 4, water quenching: take out the calcined ore, quench with deionized water to cool it down to 750°C to 800°C, repeat the calcination and water quenching steps three times, take out the ore, and quench with deionized water to cool it down to room temperature;
[0063] Step 5, drying and grinding: the ore after water quenching is placed in an oven at 105°C for 2 hours, and then ground to less than 60 mesh (0.42 mm) after cooling to room temperature;
[0064] Step 6, classification: the ground ore is screened and classified into 60 mesh (0.250 mm) to 80 mesh (0.178 mm), 80 mesh (0.178 mm) to 120 mesh (0.125 mm), 120 mesh (0.125 mm) to 170 mesh (0.09 mm), and <170 mesh (0.09 mm);
[0065] Step 7, magnetic separation: add the classified mineral materials to the magnetic separator respectively, and select them twice at a magnetic induction intensity of 1.4T;
[0066] Step 8, flotation separation: the ore materials after magnetic separation are added to the flotation machine for reverse flotation, and the flotation separation is carried out for 5 minutes under the reverse flotation conditions of pH 3, 120 g / t of dodecylamine collector, and HF as a regulator. After flotation, the quartz sand is washed with ultrapure water to neutrality, and dried (kept at 105° C. for 2 hours) to obtain quartz concentrates of different particle sizes;
[0067] Step 9, hydrothermal treatment: quartz sand concentrate, amorphous nano-SiO2 powder and alkaline solution are mixed in a certain solid-liquid ratio to obtain a mixed solution; the mixed solution is placed in a hydrothermal reactor, and a hydrothermal reaction is carried out for 24 to 48 hours under closed, constant temperature and certain saturated water vapor pressure conditions; after the reaction, the mixed solution is filtered, washed with deionized water to neutrality, and dried (keep warm at 105°C for 2 hours) to obtain quartz sand concentrate; wherein, the solid-liquid mass ratio of the quartz sand concentrate, amorphous nano-SiO2 powder and alkaline solution sodium hydroxide solution in the mixed solution is 1:2; the temperature of the hydrothermal treatment is 250°C, the pH value is ≥10, and the saturated water vapor pressure is 1.4 to 4.5MPa.
[0068] Step 10, ultrasonic acid leaching: the quartz sand concentrate after hydrothermal treatment is subjected to ultrasonic acid leaching, the ultrasonic frequency is 70KHz, the acid leaching condition is a solid-liquid mass ratio of 1:5, and a mixed acid solution is used for treatment, and the mixed acid volume ratio is V 盐酸 :V 硝酸 :V 氢氟酸 =1:1:2; the acid leaching reaction conditions are 60℃ ultrasonic assisted reaction for 120min; the quartz sand concentrate after acid leaching is rinsed with deionized water until neutral and dried (keep warm at 105℃ for 2h); wherein the mixed acid concentrations are 30% hydrochloric acid, 70% nitric acid and 40% hydrofluoric acid;
[0069] Step 11, chlorination roasting: the ore material after ultrasonic acid leaching and drying is placed in a chlorination roasting device for purification treatment, and after treatment, it is washed with 10% dilute hydrochloric acid until no Cl is detected with AgNO3. - And drying (keeping warm at 105℃ for 2h) can obtain high-purity quartz sand products with SiO2>99.996% and total impurity element content less than <38ug / g of different particle sizes; wherein, the temperature of chlorination roasting is 1200-1400℃, the time is 0.5-1h, and the chlorination gas introduced is HCl.
[0070] The above method can obtain w(SiO2)>99.996%, the total content of 12 major impurity elements is less than 38ug / g, and completely transparent quartz particles in 1g of sample account for more than 85% of the total number of quartz particles. The particle sizes are 60 mesh (0.250mm) to 80 mesh (0.178mm), 80 mesh (0.178mm) to 120 mesh (0.125mm), 120 mesh (0.125mm) to 170 mesh (0.09mm), and <170 mesh (0.09mm). High-purity quartz.
[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for processing 4N6 grade high purity quartz using granite pegmatite as raw material, characterized in that: The specific steps include: Step 1, crushing: wash the granite pegmatite until the surface is clean, first use large and medium jaw crushers to coarsely crush the ore raw materials; then use corundum liner small jaw crusher and corundum double roll crusher for fine crushing; Step 2, screening: Take the ore crushed in step 1, use a 30mm standard sieve for wet screening, and pre-select the ore materials ≥30mm through an X-ray intelligent machine and then perform the crushing and screening steps again; Step 3, calcination: place the fine-grained ore material with a particle size of less than 30 mm after screening in step 2 in a muffle furnace and heat it to 1300±10°C for 1 hour; Step 4, water quenching: take out the calcined ore, quench with deionized water to cool it down to 750°C to 800°C, repeat the calcination and water quenching steps three times, take out the ore, and quench with deionized water to cool it down to room temperature; Step 5, drying and grinding: the ore after water quenching is placed in an oven at 105°C for 2 hours, taken out and cooled to room temperature, and then ground to less than 60 mesh; Step 6, classification: the ground ore is screened and classified into 60 mesh to 80 mesh, 80 mesh to 120 mesh, 120 mesh to 170 mesh, and <170 mesh; Step 7, magnetic separation: add the classified mineral materials to the magnetic separator respectively, and select them twice at a magnetic induction intensity of 1.4T; Step 8, flotation separation: the ore materials after magnetic separation are added to the flotation machine respectively, and flotation separation is carried out for 5 minutes under the conditions of pH 3, 120 g / t of dodecylamine collector, and HF as a regulator. After flotation, the quartz sand is washed with ultrapure water to neutrality, and dried to obtain quartz concentrates of different particle sizes; Step 9, hydrothermal treatment: quartz sand concentrate, amorphous nano-SiO2 powder and an alkaline solution with a pH value of ≥10 are mixed in a solid-liquid ratio of 1:2 to obtain a mixed solution; the mixed solution is placed in a hydrothermal reactor, and a hydrothermal reaction is carried out for 24 to 48 hours in a closed state, at a constant temperature of 250°C and a saturated water vapor pressure of 1.4 to 4.5 MPa; after the reaction, the mixed solution is filtered, washed with deionized water to neutrality, and dried to obtain quartz sand concentrate; Step 10, ultrasonic acid leaching: the quartz sand concentrate after hydrothermal treatment is subjected to ultrasonic acid leaching, the ultrasonic frequency is 70KHz, the acid leaching condition is a solid-liquid mass ratio of 1:5, and a mixed acid solution is used for treatment, and the mixed acid volume ratio is V 盐酸 :V 硝酸 :V 氢氟酸 =1:1:2; the acid leaching reaction conditions are 60°C ultrasonic assisted reaction for 120 min; the quartz sand concentrate after acid leaching is rinsed with deionized water to neutrality and dried; Step 11, chlorination roasting: the ore after ultrasonic acid leaching and drying is placed in a chlorination roasting device for purification treatment, and after treatment, it is washed with 10% dilute hydrochloric acid and dried to obtain high-purity quartz sand products with SiO2>99.996% and a total impurity element content of less than 38ug / g of different particle sizes.
2. The method for processing 4N6 grade high purity quartz using granite pegmatite as raw material according to claim 1, characterized in that: In the flotation separation of step 8, reverse flotation conditions are adopted.
3. The method for processing 4N6 grade high purity quartz using granite pegmatite as raw material according to claim 1, characterized in that: The mixed acid concentrations of the ultrasonic acid leaching in step 10 are 30% hydrochloric acid, 70% nitric acid and 40% hydrofluoric acid.
4. The method for processing 4N6 grade high purity quartz using granite pegmatite as raw material according to claim 1, characterized in that: The temperature of the chlorination roasting in step 11 is 1200-1400° C., the time is 0.5-1 h, and the chlorination gas introduced is HCl.
5. The method for processing 4N6 grade high purity quartz using granite pegmatite as raw material according to claim 1, characterized in that: In step 11, the ore sample after chlorination roasting needs to be repeatedly washed with 10% dilute hydrochloric acid until no Cl can be detected with AgNO3 - .
6. The method for processing 4N6 grade high purity quartz using granite pegmatite as raw material according to claim 1, characterized in that: The drying conditions in steps 8-11 are all kept at 105° C. for 2 hours.
Citation Information
Patent Citations
Preparation method for high-purity quartz sand
CN104340981A
Method for purifying quartz by chloridizing roasting
CN111874913A
Energy-saving and environment-friendly method for preparing 4N5 high-purity quartz through efficient impurity removal
CN115092937A
Method for preparing high-purity quartz under assistance of high-alkalinity activation
CN117819556A
Treatment method for purifying quartz sand through suspension chloridizing roasting
CN117985725A